2022
DOI: 10.1002/ange.202208168
|View full text |Cite
|
Sign up to set email alerts
|

Giant Multi‐Photon Absorption by Heptazine Organometalation

Abstract: Multi‐photon absorption (MPA) is of increasing interest for applications in technologically important “windows” of the electromagnetic spectrum (near‐infrared III, NIR‐III, 1550–1870 nm; and the new 2080–2340 nm region); however, few molecules exist that display strong MPA at these long wavelengths. We herein report the syntheses of the first 2,5,8‐s‐heptazine‐cored organometallic complexes, together with organic analogues. The complexes exhibit outstanding 3PA cross‐sections in the NIR‐III and exceptional 4PA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…The aforementioned results further demonstrated that CuSAC6N6 not only had a peroxidase-like Cu-N coordination active center but also owned an unusual donor-πacceptor (D-π-A) unit (Fig. 1h), [62][63][64] where the single Cu atom acted as an electron acceptor, the triazine rings emerged as electron donors (photovoltaic center), and the -N=CH-CH=N-linkers offered π-conjugated charge transfer channels for D-A couples. These π-interconnected D-A couples played a crucial role in addressing the inconsistency of requirements for basic and gain reactions by not only reducing recombination (control sample: Cu 2+ -PCN) and promoting charge separation (control sample: Cu-N-C), but also accelerating intramolecular charge transfer (control sample: Cu-N-C/CNmw).…”
Section: Coordinated Basic and Gain Reactions Mechanism Of Cusac6n6mentioning
confidence: 81%
“…The aforementioned results further demonstrated that CuSAC6N6 not only had a peroxidase-like Cu-N coordination active center but also owned an unusual donor-πacceptor (D-π-A) unit (Fig. 1h), [62][63][64] where the single Cu atom acted as an electron acceptor, the triazine rings emerged as electron donors (photovoltaic center), and the -N=CH-CH=N-linkers offered π-conjugated charge transfer channels for D-A couples. These π-interconnected D-A couples played a crucial role in addressing the inconsistency of requirements for basic and gain reactions by not only reducing recombination (control sample: Cu 2+ -PCN) and promoting charge separation (control sample: Cu-N-C), but also accelerating intramolecular charge transfer (control sample: Cu-N-C/CNmw).…”
Section: Coordinated Basic and Gain Reactions Mechanism Of Cusac6n6mentioning
confidence: 81%